2017
DOI: 10.3389/fpls.2017.00570
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Analyses Shed Light on the Response of Sargassum vulgare to Ocean Acidification at Different Time Scales

Abstract: Studies regarding macroalgal responses to ocean acidification (OA) are mostly limited to short-term experiments in controlled conditions, which hamper the possibility to scale up the observations to long-term effects in the natural environment. To gain a broader perspective, we utilized volcanic CO2 vents as a “natural laboratory” to study OA effects on Sargassum vulgare at different time scales. We measured photosynthetic rates, oxidative stress levels, antioxidant contents, antioxidant enzyme activities, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 94 publications
2
23
0
Order By: Relevance
“…Indeed, the concentrations of Corg were strongly correlated to sediment fines percentage, whereas Cinorg was associated to sediment density and pH (Table 3). The positive correlation between Cinorg and pH (Table 3) may be explained by the reduction or disappearance of crustose coralline algae at low pH values (6.7 ≤ 8.0), and as a consequence, the loss of the sediment carbonate fraction, as previously described [45][46][47] for studies on volcanic marine CO 2 vents in the sea around Ischia Island. Likewise, researchers [48] found that pH had a strong correlation with Cinorg produced from the small microcalcareus macroalgae belonging to the epiphytic genera Pneophyllum, Hydrolithon, and Melobesia, which grow on the largest macroalgae and aquatic angiosperms of the Italian TWS.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, the concentrations of Corg were strongly correlated to sediment fines percentage, whereas Cinorg was associated to sediment density and pH (Table 3). The positive correlation between Cinorg and pH (Table 3) may be explained by the reduction or disappearance of crustose coralline algae at low pH values (6.7 ≤ 8.0), and as a consequence, the loss of the sediment carbonate fraction, as previously described [45][46][47] for studies on volcanic marine CO 2 vents in the sea around Ischia Island. Likewise, researchers [48] found that pH had a strong correlation with Cinorg produced from the small microcalcareus macroalgae belonging to the epiphytic genera Pneophyllum, Hydrolithon, and Melobesia, which grow on the largest macroalgae and aquatic angiosperms of the Italian TWS.…”
Section: Discussionsupporting
confidence: 64%
“…To our knowledge, there are only very few studies dealing with the effect of CO 2 -induced acidification of seawater on the antioxidative potential of micro- and macroalgae. Acidification increased the MDA content of a diatom ( Thalassiosira weissflogii ) and a brown seaweed species ( Sargassum vulgare) , indicating that membrane lipid peroxidation was enhanced [ 98 , 99 ]. Additionally, the induction of SOD in S. vulgare under acidified conditions points to its major role in preventing ·O 2 − overproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the induction of SOD in S. vulgare under acidified conditions points to its major role in preventing ·O 2 − overproduction. Kumar et al [ 99 ] found, for S. vulgare , a higher energy metabolism after exposure to low pH conditions at volcanic CO 2 vents. The study by Iñiguez et al [ 100 ] revealed on the molecular level that CO 2 enrichment induced only very few transcriptomic changes (e.g., induction of transcripts coding for RuBisCO rbcL ) in the brown seaweed Desmarestia anceps .…”
Section: Discussionmentioning
confidence: 99%
“…However, even those species with active CCMs may benefit from increased pCO 2 if they utilize directly CO 2 instead of HCO 3 − as a carbon source. Previous pH drift experiments have revealed that S. vulgare populations at acidified and control sites have active CCM (Kumar, AbdElgawad, et al, 2017). Our results are in line with a recent comparative proteomic study showing enrichment of proteins involved in photosynthesis in the natural population of the seagrass Cymodocea nodosa in the CO 2 vents at Vulcano Island (Piro et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Marine areas characterized by natural CO 2 vents represent useful “natural laboratories” to investigate the impact of OA on macroalgae in their natural habitat (Dahms et al, 2018; Kumar, AbdElgawad, et al, 2017; Kumar et al, 2018, 2020; Kumar, Castellano, et al, 2017). Off the Island of Ischia, along the Castello Aragonese, natural underwater vents of volcanic origins release gases, mainly CO 2 , causing seawater acidification (Hall‐Spencer et al, 2008) and offering a unique opportunity to investigate the long‐term effects of OA.…”
Section: Introductionmentioning
confidence: 99%